Dealing with disturbances: Intervention and adaptation in Finnish neighbourhoods - Antti Kouvo; Risto Haverinen (Sage Publishers Ltd., 2025)
This article investigates neighbourhood social dynamics with the help of two attitude dimensions discovered in earlier qualitative research: the threshold of intervention and adaptation. The data come from a nationally representative Finnish Neighbourhood Survey (N = 760) conducted in 2012. Our results show that adaptation and intervention characterise neighbourhood interaction in our survey data set as well. The threshold of intervention is higher among the residents of detached houses and those without strong ties in the neighbourhood. Adaptation is associated with low income and living in a detached house. However, different types of neighbours created on the basis of adaptation and intervention provide a richer picture of the phenomenon and more powerful explanations. The suggestions for future research and theoretical implications of the results are discussed.